Pregnancy Outcome in First Trimester Bleed - Hajra Sayyad, Humaira Jadoon, Maria Gul, Maryam Bibi, Salma Rehman, Seemab Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There is disagreement on the outcome of vaginal bleeding during the first trimester. The purpose of this study was to ascertain the perinatal and maternal outcome for patients who presenting with vaginal bleeding during the first trimester. Methods: Over the course of a year, 1007 women with vaginal bleeding in the first trimester were included in this prospective observational study at a tertiary care hospital in Peshawar. The diagnosis was confirmed by a USG and a thorough history. All of these patients had their outcomes assessed, including spontaneous, threatened abortions, incomplete, and complete abortions, subchorionic hematoma, intrauterine foetal death, missed abortions, bleeding in the second and third trimesters, pre-mature rupture of membranes, intra-uterine growth restriction, and preterm births. Results: 1007 individuals with 11835 confinements had vaginal bleeding in first trimester. The age range of 21 to 30 years saw the highest occurrence (52.3%). First trimester haemorrhage was detected in 63.9 percent of primigravidas compared to 36.1 percent of multigravidas. It was shown that only 7% of patients who attended after 10 weeks had an abortion, compared to 76.9% of patients who presented before 6 weeks. In the 163 patients who continued to be pregnant after experiencing vaginal bleeding in first trimester, 1.8 percent had an abortion in the 2nd trimester, and 15.3% experienced premature labour. 6.75 percent of pregnancies end prematurely, and 1.8% experience antepartum haemorrhage. Conclusions: First trimester vaginal bleeding foretells ancillary maternal and foetal difficulties, according to the findings of the current study. Additionally, as clinical intervention plays a crucial part in preserving pregnancy and lowering foetal problems, careful supervision and planning by the doctor are crucial. Keywords: First trimester bleeding, Abortions, Threatened abortion, Preterm Labor,